Strategi coping dalam mengatasi kecemasan terhadap korban kekerasan seksual - Aprasanjani, Baiq Ashri Firda; Ardhani, Tristiadi Ardhi (Maliki Interdisciplinary Journal, 2024)
Anxiety that arises as a result of experiencing sexual violence can be suppressed with the application of appropriate coping strategies. However, individuals who are victims of sexual violence often use less effective coping strategies, which can potentially worsen their condition and lead to maladaptive situations. By applying effective coping strategies such as Problem-Focused Coping (PFC) and Emotion-Focused Coping (EFC), the level of anxiety can be reduced and managed. PFC is designed to address or change the source of stress directly, while EFC focuses on changing the emotional response to stress. In the context of individuals who are victims of sexual violence, the application of effective coping strategies can help them in increasing self-confidence, reducing anxiety, and even assisting individuals in the process of healing trauma. Therefore, understanding and applying effective coping strategies are very important in supporting the recovery process of sexual violence victims as a whole. Thus, this approach shows how important education and support are in helping individuals who experience sexual violence to develop and apply effective coping strategies.